Empleo de rizobacterias como promotores de crecimiento vegetal en la asociación del pasto azul (dactylis glomerata l.) con alfalfa (medicago sativa) y trébol rojo (trifolium pratense) - Espín Ramírez, Luis Ernesto (2012)
Pastures and fodder are the staple food of cattle and other grazing use efficiency could meet much of the nutritional requirements of livestock. This research was conducted in the parish of the canton Marcos Espinel Píllaro Tungurahua province lasted 60 days as a general objective determine the microbial population in the association of grasses and legumes by inoculation of plant growth promoting rhizobacteria as Inoculate specific objective the plant growth promoting rhizobacteria: chroococum Azotobacter, Azotobacter vinelandii, Azotobacter and Pseudomonas beijerinckii paspali fluorescens in grass-legume associations in study, using a completely randomized design (CRD) with two associations of grasses, five inoculants and two crop ages . The best at what corresponds to the interaction of grass + legume inoculants x age x can be seen that there is interaction at 45 days with the Blue Grass + Blue Grass + Alfalfa and Clover with the inoculant A. Chroococum with 20.17 cm and 20.33 cm, followed by the witness within 45 days with 21.17 cm and 20.83 cm, with regard to the interaction Pasto + legume inoculants x age x can be seen that there is interaction at 60 days with the Blue Grass + Alfalfa and clover and blue + inoculant A. vinelandii with 18.33 cm and 17.33 cm, followed by Witness at 60 days with 18.67 cm and 17.67 cm. It can be seen that within the interaction results in the Grass & Legume x inoculant x age interaction is reflected at 45 and 60 days with the Blue Grass + Blue + Alfalfa and Clover and the inoculant A. Vinelandii with (7.50 cm and 7.86 cm) (2.33 cm and 2.67 cm) at Pasto Interaction + legume inoculants x x age interaction reflected in the Blue Grass + Blue + Alfalfa and clover at 60 days with the inoculant P. fluorescens with 3.33 (g) and 3.83 (g) Witness inoculant followed by 60 days with 4.17 (g) and 4.50 (g) and turn in the Grass & Legume inoculants x age x can be seen that there is interaction in Alfalfa and grass Blue + Blue + Shamrock at 60 days with the inoculant A. 5.33 and Chroococum with 5.50 g. With regard to the best results from the interaction grass + legume inoculants x age x can be seen that there is interaction at 45 days with the Blue Grass + Blue + Alfalfa and clover inoculant A. 20.17 and 20.33 Chroococum with g, in total forage research on the interaction Pasto + legume inoculants x x age interaction shows that there are 45 days in the Bluegrass Blue + + Alfalfa and clover inoculant A. 102.50 and 117.20 vinelandii with